Biology and stock assessment of the pharaoh cuttlefish, Sepia pharaonis Ehrenberg, 1831 from the Arabian Sea off Oman - A Al, Marzouqi; Jayabalan, N; Al Nahdi, A (Indian Journal of Fisheries, 2016)
A study on the biology, population parameters and stock assessment of the pharaoh cuttlefish Sepia pharaonis Ehrenberg,1831 was carried out from the Arabian Sea off Oman during 2001-2002. The mantle length - total weight relationship forpooled sexes was 0.4067ML2.5164. The population of S. pharaonis spawned between August and December as well asduring April and May. The monthly gonado-somatic indices (GSI) and relative condition factor (Kn) in males and femaleswere high during spawning months. Males were dominant over females (M:F=1:0.87) in commercial landings. The lengthat first maturity for males was 19.0 cm of mantle length and females matured at 20.2 cm. The estimated von-Bertalanffygrowth parameters were: Lâˆž = 46.5 cm; K = 1.04 y-1 and t0 = -0.13. The total mortality (Z), natural mortality (M) andfishing mortality (F) coefficients were 2.0 y-1, 1.52 y-1 and 0.48 y-1 respectively. The MSY calculated stood at 9,608 t. Theexploitation rate (E) was 0.24. The Yw/R increased considerably up to F=1.8. The B/R at F=1.9 for Lc 16 cm (0.27 kg)could be obtained at F=4 for an increased Lc of 20.8 cm. The plot of relative yield indicated the stock to be nearly depletedat F = 3.0, when Lc was 16 cm. However, the stock would withstand an F up to 4 at the Lc of 20.8 cm. The currentexploitation pattern indicates scope for further expansion of the fishery.